Chemical screening and mosquitocidal activity of essential oil derived from Mikania scandens (L.) Willd. against Anopheles gambiae Giles and their non-toxicity on mosquito predators. Issue 1 (31st December 2023) - Radhakrishnan, Narayanaswamy; Karthi, Sengodan; Raghuraman, Pandiyan; Ganesan, Raja; Srinivasan, Kumaraswamy; Edwin, Edward-Sam; Ganesh-Kumar, Selvaraj; Mohd Esa, Norhaizan; Senthil-Nathan, Sengottayan; Vasantha-Srinivasan, Prabhakaran; Krutmuangh, Patcharin; Alwahibi, Mona S.; et al.
Abstract : In-vitro chemical characterization and mosquitocidal screening of essential oil derived from Mikania scandens (L.) Willd. (Asteraceae) (CVO-MS) against the malarial vector Anopheles gambiae was investigated. GC-MS analysis evidenced a total of 12 bio-active compounds, and maximum at α-bisabolol (39.34%) followed by stigmasterol (13.45%) respectively. The larvicidal activity of CVO-MS against the malarial vector An. gambiae evidenced that the mortality rate was prominent at the maximum dosage of 1000 ppm. The Median Lethal Concentration (LC50 ) of CVO-MS was established at 488 ± 2.45 ppm, respectively. Enzyme inhibition assay showed that the CVO-MS delivers a significant upsurge in the level of CYP450, GST, and a decline in the level of α-β carboxylesterase activity in both the third and fourth instar ( p ≤  0.0001). The gut-histological examination of CVO-MS showed that there is severe damage in the mid-gut tissues, especially epithelial layer (EL), gut-lumen (GL), and peritrophic membrane (pM). The non-target screening against the mosquito predators ( A. bouvieri, D. indicus, and third instar larvae of Tx. splendens ) suggests that CVO-MS showed less toxicity as compared to Pestanal® (1 ppm) respectively. The present study has paved a new insight in understanding the bioactivity of CVO-MS as a potential larvicidal agent of malarial vector and non-toxic against mosquito predators.